Preventive Effects of Salacia reticulata on Obesity and Metabolic Disorders in TSOD Mice. (23rd June 2011) - Akase, Tomoko; Shimada, Tsutomu; Harasawa, Yukiko; Akase, Tomohide; Ikeya, Yukinobu; Nagai, Eiichi; Iizuka, Seiichi; Nakagami, Gojiro; Iizaka, Shinji; Sanada, Hiromi; Aburada, Masaki
Abstract : The extracts of Salacia reticulata ( Salacia extract), a plant that has been used for the treatment of early diabetes, rheumatism and gonorrhea in Ayurveda, have been shown to have an anti-obesity effect and suppress hyperglycemia. In this study, the effects of Salacia extract on various symptoms of metabolic disorder were investigated and compared using these TSOD mice and non-obese TSNO mice. Body weight, food intake, plasma biochemistry, visceral and subcutaneous fat (X-ray and CT), glucose tolerance, blood pressure and pain tolerance were measured, and histopathological examination of the liver was carried out. A significant dose-dependent decline in the gain in body weight, accumulation of visceral and subcutaneous fat and an improvement of abnormal glucose tolerance, hypertension and peripheral neuropathy were noticed in TSOD mice. In addition, hepatocellular swelling, fatty degeneration of hepatocytes, inflammatory cell infiltration and single-cell necrosis were observed on histopathological examination of the liver in TSOD mice. Salacia extract markedly improved these symptoms upon treatment. Based on the above results, it is concluded that Salacia extract has remarkable potential to prevent obesity and associated metabolic disorders including the development of metabolic syndrome.